1995
DOI: 10.1164/ajrccm.152.1.7599845
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of multidrug-resistant tuberculosis in a large urban setting.

Abstract: Multidrug resistance has become an increasingly important problem in the control and prevention of tuberculosis in large urban centers. Although several small outbreaks of multidrug-resistant (MDR) tuberculosis in New York City have been reported, the increase in the number of cases is not fully explained by these recognized outbreaks, and the modes of transmission have not been clearly delineated. Transmission patterns of MDR tuberculosis in New York City, therefore, were studied by stratifying Mycobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…DNA fingerprinting of Mycobacterium tuberculosis has been used in population-based studies to determine the proportion of recently transmitted disease and to assess risk factors associated with recent transmission (1,4,5,6,7,8,10,13,14,17,19,20). These studies were carried out mostly in countries with a low prevalence of tuberculosis (1,4,5,6,7,10,14,17,20), while a few were done in countries with a high prevalence of tuberculosis and human immunodeficiency virus (HIV) infection (13,16,19).…”
mentioning
confidence: 99%
“…DNA fingerprinting of Mycobacterium tuberculosis has been used in population-based studies to determine the proportion of recently transmitted disease and to assess risk factors associated with recent transmission (1,4,5,6,7,8,10,13,14,17,19,20). These studies were carried out mostly in countries with a low prevalence of tuberculosis (1,4,5,6,7,10,14,17,20), while a few were done in countries with a high prevalence of tuberculosis and human immunodeficiency virus (HIV) infection (13,16,19).…”
mentioning
confidence: 99%
“…Importantly, transmission was not limited to these high risk groups as there was a "spill over" to the general population. Other studies on transmission of TB in large urban settings through cluster analysis (Alland et al 1994, Small et al 1994, Friedman et al 1995a, Sepkowitz et al 1995 demonstrated that besides drug resistance, young age, race, social status and being health care worker are risk factors.…”
Section: Applications Of Molecular Strain Typing As An Additional Toomentioning
confidence: 99%
“…19 These also spread by the airborne route. 20 Guidance for how to cure people sick with DR-TB and stop further spread has been available for nearly 20 years. [21][22][23][24] Low and middle income countries bear the greatest burden of TB and DR-TB.…”
Section: Introduction Burden Of Tuberculosis (Tb) and Drug Resistancementioning
confidence: 99%